2006
DOI: 10.1093/brain/awl305
|View full text |Cite
|
Sign up to set email alerts
|

Epilepsy surgery involving the sensory-motor cortex

Abstract: Our aim was to assess the outcome with regard to seizures and neurological function in unselected patients undergoing resective surgery involving the perirolandic area, with or without multiple subpial transections (MSTs). All patients who underwent perirolandic cortical resection or MSTs from 1979 to 2003 at the London Health Sciences Centre were identified. Patients were included if they had seizures originating in the perirolandic area, recorded with subdural electrodes, or if they had scalp recorded seizur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
54
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(62 citation statements)
references
References 39 publications
7
54
0
1
Order By: Relevance
“…32 Importantly, this represents a reduction in deficits over conventional resections in our study, and in previous studies that have reported postoperative neurological deficits ranging from 50% to 83%. [1][2][3]25 Hence, our results demonstrate that iMRI-assisted resections are less prone to incurring neurological deficits. This may be due, in part, to the surgeon undertaking a more conservative extirpation with the knowledge that iMRI may provide a "second chance" to reevaluate the surgical course of action; thus in cases of FCD adjacent to eloquent cortex this minimizes the risk of damage to functional regions and enhances postoperative quality of life.…”
Section: Discussionsupporting
confidence: 56%
“…32 Importantly, this represents a reduction in deficits over conventional resections in our study, and in previous studies that have reported postoperative neurological deficits ranging from 50% to 83%. [1][2][3]25 Hence, our results demonstrate that iMRI-assisted resections are less prone to incurring neurological deficits. This may be due, in part, to the surgeon undertaking a more conservative extirpation with the knowledge that iMRI may provide a "second chance" to reevaluate the surgical course of action; thus in cases of FCD adjacent to eloquent cortex this minimizes the risk of damage to functional regions and enhances postoperative quality of life.…”
Section: Discussionsupporting
confidence: 56%
“…3) On the other hand, in a study of patients with epilepsy undergoing resection surgery involving the primary sensorimotor cortex, post-surgical permanent deficits were reported in 50% of the study cohort. 43) All these studies employed the best available methods for mapping and monitoring to achieve safe, maximal tumor resection. Further analysis is needed to eliminate confounding factors related to surgical indications and patient selection, but these results seem to indicate that gliomas located in or near the eloquent brain areas were treated by the surgical operation relevant for the disease stage that promoted functional recovery.…”
Section: Evaluation Of Brain Function For the Surgical Resection Of Gmentioning
confidence: 99%
“…For the 6 patients who underwent three iMRI scans, the seizure outcome is not ideal, but most of them (5 out of 6 patients) developed none-hemiparesis. Fewer times of iMRI (once and twice) were performed for the other 25 patients, most of whom achieved (18) reported that 55 patients with epilepsy involved perirolandic area underwent a resection surgery with or without multiple subpial transections (MSTs), and 50% of patients developed permanent post-surgical deficits. Despite the variation in procedures of preoperative assessment, durations of follow-up survey, and individual difference of patients (e.g.…”
Section: Times Of Imri Scansmentioning
confidence: 99%